Surfaces generated by the real and imaginary parts of analytic functions: $A$-deformations occurring independently or simultaneously - Bezkorovaina, L. L. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
It is proved that the surfaces generated by the real and imaginary parts of analytic functions allow nontrivial infinitesimalareal deformations of certain three types. The fields of displacements are explicitly expressed in all three cases. Givensurfaces are rigid with respect to infinitesimal bendings of each type.